PERANAN PEREMPUAN DALAM MEMBINA KESADARAN BERAGAMA ANAK - Nursyam, Nursyam (Pusat Studi Gender dan Anak, IAIN Palu, 2018)
Children are a gift from Allah SWT that is always expected by every family. However, not everyone (parents) can take good care of their children according to what is commanded by Allah through religious teachings. For various reasons and reasons, parents no longer pay attention to children's religious education. In the end, the negative impact will be felt by parents even more so for their own children. To be able to form a religious awareness of children, the mother as the first person known to the child, then the mother needs to provide an understanding of the religious dimension of children is important, the child is essentially a mandate from Allah SWT that must be grateful, and we as Muslims must carry out the mandate with good and right. The way to be grateful for the gift of God in the form of children is through caring for, caring for, and educating and coaching the characters properly and correctly, so that they will not become weak children, both physically and mentally, and weak in faith and weak in their worldly lives. The aim of education is to be a perfect Muslim, who has faith and fear Allah. Mother as a parent is the first primary educator for children, before the child knows the outside world, first the child knows the mother and after that his father is the closest person to the child. As for women's efforts in fostering religious awareness as follows: to destroy personality, to form good habits , forming civilizations in the Muslim world and helping to encourage them to encourage things that lead to obedience to God and educate them with different ways of worship. Like prayer, recitation, prayer at home and at school.